DOES IDEOLOGY (STILL) MATTER? YOUTH VOTERS BEHAVIOR ANAYLISIS AT THE NATIONAL LEGISLATIVE ELECTION IN GATAK DISTRICT, CENTRAL JAVA - Hamsah, Dimar Tidi; Ilham, Teguh; Safitri, Dewi (Fakultas Politik Pemerintahan, 2023)
This study aims to determine the characteristics and analyze the behavior of youth voters in the 2019 legislative general election (DPR) in Gatak District, Sukoharjo Regency, Central Java Province, Indonesia. The method used is a mixed method. The population is youth voters aged 20-24 years and the number of samples is 97 voters determined by the Slovin formula and selected using a simple random technique. Test the validity of the questionnaire using the Guttman scale. In addition, this study also used semi-structured interviews with nine selected informants. Secondary data is also used to complete the analysis, such as: reports, scientific writings, and news. This study found that based on the typology, youth voters in Gatak District tended to be rational, not traditional, not skeptical, however, they tend not to be critical voters, especially on two indicators related to attachment to the ideology of political parties and their legislative candidates. Based on these results, it is concluded that the preferences of youth voters towards parties and candidates are more policy problem solving oriented than ideological orientations.